The Roman wedding : ritual and meaning in antiquity - Hersch, Karen K., 1968- (Cambridge, U. K. : Cambridge University Press, 2010)
'This is the first book-length examination of Roman wedding ritual'--Provided by publisher.
'The wedding ritual of the ancient Romans provides a crucial key to understanding their remarkable civilization. The intriguing ceremony represented the starting point of a Roman family as well as a Roman girl's transition to womanhood. This is the first book-length examination of Roman wedding ritual. Drawing on literary, legal, historical, antiquarian, and artistic evidence of Roman nuptials from the end of the Republic through the early Empire (from ca. 200 BC to 200 AD), Karen Hersch shows how the Roman wedding expressed the ideals and norms of an ancient people. Her book is an invaluable tool for Roman social historians interested in how ideas of gender, law, religion, and tradition are interwoven into the wedding ceremony of every culture'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Marriage customs and rites -- Rome -- History; Weddings -- Rome -- History; Rome -- Social life and customs